Comparison of news and sirs score for early recognition of sepsis in medicine department - Fatima, Gulzar; Kumar, Sooraj; Lata; Shah, Muhammad Iqbal; Bai, Poona; Sajjad, Hira (Infectious Diseases Journal of Pakistan, 2025)
Background: By alerting doctors and nurses to patients who are deteriorating, an early warning score system enables them to promptly address adverse events. It is not clear as to which scoring system is better in patients with sepsis16. Therefore, the current study aimed to compare the predictive accuracy of NEWS and SIRS in terms of early diagnosis of sepsis. Material and Methods: It was a cross-sectional study, conducted at the General Medicine Department, LUMHS, Hyderabad/Jamshoro, from Aug/2025 till Oct/2025. A total of 105 patients who fulfilled the selection criteria were included. SIRS and NEWS were applied as screening tools for early prediction of sepsis. Sepsis was confirmed based on the Sepsis-3 definition. Findings were noted down and were subjected to statistical analysis. Results: The median (IQR) age of the patients was 41 (12) years. Sepsis was diagnosed by Sepsis-3 criteria in 58 (55.2%) patients. According to the NEWS, 53 (50.5%) had a high risk of sepsis and according to the SIRS score, 55 (52.4%) patients had a positive SIRS score for sepsis. The sensitivity, specificity, PPV, NPV and predictive accuracy of NEWS keeping Sepsis-3 as diagnostic was 81.2%, 87.1%, 88.7%, 78.7% and 83.8%, respectively, and for SIRS score, it was 75.9%, 76.5%, 79.9%, 72.1% and 76.2%. Conclusion: For predicting sepsis, NEWS was associated with higher sensitivity, higher specificity and predictive accuracy as compared to SIRS. Keywords: Critical care, NEWS, Sepsis, SIRS